Frequency of Poor & Good Coronary Collateral Circulation in patients of Non-ST Segment Elevation Myocardial Infarction & to compare mean Platelet –Lymphocyte ratio with good & poor coronary collateral circulation - Raza, Ahmad; Sharif, Asma; Fayyaz Zafar, Muhammad; Azeem, Shahzad; Arslan Aslam, Muhammad (Pakistan Journal of Medical & Health Sciences, 2022)
Background: Coronary collateral circulation (CCC) is a secondary source of blood supply to an ischemic myocardial area in coronary artery disease. One of the most important protective responses of the cardiac against ischemia is the development of CCC. Recently, platelet to lymphocyte ratio has emerged as a major inflammatory marker & a new predictor of serious unfavorable cardiovascular outcomes. Aim: To find the frequency of poor & good coronary collateral circulation in patients of Non-ST Segment Elevation Myocardial Infarction & to compare mean platelet–lymphocyte ratio in patients with poor & good coronary collateral circulation of Non-ST Segment Elevation Myocardial Infarction. Methodology: This cross Sectional study was conducted in Cardiology Department, Mayo Hospital Lahore After taking informed consent 150 patients meeting inclusion criteria was taken in this study. The patients were enrolled from Department Cardiology, Mayo Hospital Lahore. Their basic demographical information like age, gender and contact detail was obtained. Patients were labeled as according to CCC, one with Poor CCC and second with good CCC [as per operational definition]. All procedure was done by consultant cardiologist having more than 5 years of experience after post-graduation. Venous blood was collected from patients in sterilized manners by experienced staff nurse and was sent to hospital laboratory for analysis of PLR. PLR was compared in cases with good and poor CCC. Results:1The average age of cases was 52.41 ± 18.12 years with minimum and maximum age of 20 and 80 years. There were 96(64%) male and 54(36%) female cases in this study. A total of 33 (22%) cases had poor and 117(78%) cases had good CCC. The mean Platelet-to-lymphocyte ratio (PLR) was 122.16 ± 30.10 with minimum and maximum PLR was 80.64 and 201.60. The mean PLR in cases with poor and good CCC was 165.95±21.93 and 109.81 ± 18.21 respectively, the mean PLR was highly significant in cases with Poor CCC when compared with good CCC, p-value < 0.0001. Conclusion: This study concludes that cases with poor CCC have higher PLR when compared to good CCC, so in future cases with higher PLR at admission can be predict for high risk patients for poor CCC. Using PLR (inexpensive and readily available) test we can hence, patients with NSTEMI can be prevented from morbidity & mortality by early and appropriate medications or interventions.